Studies In Modern Italian History: From The Risorgimento To The Republic - Coppa Frank J (Peter Lang Publishing Inc, 1986)
Italy's Fascist experience and role in World War II sparked a reassessment of Italian developments since unification. The peninsula's strategic position, its role in NATO and the European Economic Community, the remaking of postwar democracy, as well as a range of problems confronting the Italian Republic, all mandate a reassessment of its past. The thirteen essays in this work are divided into four sections which focus upon the Risorgimento, the Liberal Age, the Fascist Era, and the postwar Republic. The contributors include Emiliana P. Noether, Raymond Grew, Frank J. Coppa, Ronald S. Cunsolo, Spencer Di Scala, Alexander De Grand, Richard Drake, Joel Blatt, Sandi E. Cooper and John Thayer from the United States as well as Salvo Mastellone, Emilio Gentile, and Luigi di Rosa from Italy.